An Ecofriendly and Stability-indicating RP-HPLC Method for Determination of Dapsone: Application to Pharmaceutical Analysis - Lida Beheshti-Maal (Science Faculty of Chiang Mai University, 2019)
A green and stability-indicating RP-HPLC method was developed for determination of dapsone in pharmaceutical preparations. The separation was based on a C18 analytical column. The mobile phase consisted of formic acid solution (pH =3):ethanol (90:10, v/v). In forced degradation studies, the drug was subjected to oxidation, hydrolysis, photolysis and heat. Among the different stress conditions, the exposure to light (UV-C and sunlight) was found to be an important adverse stability factor. The drug exhibited degradation in both irradiation experiments affording a common photoproduct. The applied procedure was found to be linear in concentration range of 0.2-50 µg/mL (r2= 0.9999). Precision was evaluated by replicate analysis in which % relative standard deviation values for areas were found to be below 2.0. The recoveries obtained (99.50-101.38%) ensured the accuracy of the developed method. The peak of dapsone was well resolved from the photoproduct as well as the pharmaceutical excipients. Accordingly, the proposed validated and sustainable procedure was proved to be proper for routine analyzing and stability studies of dapsone in pharmaceutical formulations.